Awareness and practices among dairy producers and consumers in Sri Lanka - Gedara, Pradeepa Korale; Roy, Devesh; Sonkar, Vinay Kumar; Weerahewa, Jeevika; Kanthilanka, Hemali; Hemachandra, Dilini; Vithanage, Kasun; Rathnasekara, Hasara; Boss, Ruchira (International Food Policy Research Institute, 2021)
Provision of food safety requires not only regulation but also a demand pull where value chain participants demand food safety or are able to play their role in providing safe food. In both cases, producer, and consumer awareness about requirements for food safety is a precondition for delivery of food safety. In this paper, focusing on dairy in Sri Lanka, we assess the awareness and choice of practices by producers and consumers towards food safety. Sri Lanka has unique features in the dairy sector, with very high import penetration and form of consumption, i.e., powdered milk, that actuates formalization. Looking at different segments of the population, including rural, urban and estate, and different management systems, the evidence suggests only a moderate level of food safety awareness in dairy in middle-income consumers in Sri Lanka. Considering the differences across systems, the degree of adoption of food safety is lowest among farmers in the extensive system, while it is highest among farmers in the intensive system. However, in terms of choice between powdered and fresh milk, food safety consciousness is one of the most significant determinants where fresh milk is considered comparatively unsafe. Even when food safety issues arose in powdered milk, only small adjustments occurred in consumption, both because the health effects were limited, and the choice sets were circumscribed by the number of brands across which some consumers switched following the food safety scare. In the push toward promotion of fresh milk consumption, ensuring food safety and convincing consumers about merits of fresh milk would be required in Sri Lanka beyond the preference change from well-established powdered milk consumption.